2020
DOI: 10.1016/j.celrep.2020.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diversity of Glycinergic Commissural Inhibitory Neurons in Larval Zebrafish

Abstract: Graphical Abstract Highlights d dI6dmrt3a and V0d neurons are commissural inhibitory neurons in zebrafish d dI6dmrt3a and V0d neurons are cooperatively involved in leftright alternation d dI6dmrt3a and V0d neurons are recruited at different frequencies of swimming d Ablation of dI6dmrt3a neurons impairs regular left-right alternation SUMMARY Commissural inhibitory neurons in the spinal cord of aquatic vertebrates coordinate left-right body alternation during swimming.Their developmental origin, however, has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(106 citation statements)
references
References 49 publications
(88 reference statements)
7
92
0
Order By: Relevance
“…Conversely, the gene profile of single glyt2 + /dbx1b + neurons collected from the gray matter overlapped mostly with n 2 ( Figure 4F). The latter neurons correspond to the V0d interneuron population described previously in this zebrafish line (Satou et al, 2012(Satou et al, , 2020. We therefore performed a more detailed analysis of n 1 corresponding to the lateral neurons of the spinal enlargements.…”
Section: Molecular Profiling Reveals Specialized Intraspinal Propriocmentioning
confidence: 95%
See 2 more Smart Citations
“…Conversely, the gene profile of single glyt2 + /dbx1b + neurons collected from the gray matter overlapped mostly with n 2 ( Figure 4F). The latter neurons correspond to the V0d interneuron population described previously in this zebrafish line (Satou et al, 2012(Satou et al, , 2020. We therefore performed a more detailed analysis of n 1 corresponding to the lateral neurons of the spinal enlargements.…”
Section: Molecular Profiling Reveals Specialized Intraspinal Propriocmentioning
confidence: 95%
“…A servomechanism for efficient locomotor behavior Next we examined whether the movement-encoded inhibitory feedback signal from ILP neurons is integrated in the central locomotor network. Our analysis focused on three core components of the zebrafish locomotor network: motor neurons (Ampatzis et al, 2013;Gabriel et al, 2011;Song et al, 2016), rhythm-generating excitatory V2a interneurons (Ampatzis et al, 2014;Ausborn et al, 2012;Ljunggren et al, 2014;Eklö f-Ljunggren et al, 2012;Song et al, 2018Song et al, , 2020, and left-right-coordinating inhibitory V0d interneurons (Satou et al, 2020), which were recorded during movement-induced activation of ILP neurons in the isolated spinal cord. In motor neurons, no response was induced by bending of the spinal cord in either direction ( Figure 7A).…”
Section: Ll Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered the possibility that as V1 axons ascend and travel dorsally, they connect targeted ventral horn commissurally projecting neurons that are likely dI6/V0 identity. These neurons comprise both inhibitory and excitatory [52][53][54] subsets but are characterized by a common morphological motif: a commissural, bifurcating axonal trajectory 52,53 . We utilized this distinct morphology to categorize these neurons as Commissural Pre-motor (CoPr) neurons.…”
Section: Copa Neurons Receive Both Local and Distal V1 Inhibitionmentioning
confidence: 99%
“…Genetic ablation studies in mice showed that the two major subclasses are recruited in a frequency-dependent manner during locomotion; the inhibitory V0D INs are more active at low speeds and the excitatory V0V interneurons at higher frequencies [2]. However, a recent study in larval zebrafish showed that, in contrast to mice, V0D INs are important at higher frequencies [7]. Much remains to fully understand and characterize V0 IN subtypes and their role in locomotor circuits.…”
Section: V0 Ins Include a Large Proportion Of Cells Having Commissuramentioning
confidence: 99%